Factores sociolaborales y el conocimiento de la enfermera sobre manejo de víctimas de desastre, Hospital Belén de Trujillo - Carrera Enriquez, Flor de Maria Isabel (2021)
The objective of the non-experimental, descriptive, cross-sectional research study was carried out to determine the Socio-labor Factors and the Nurse's Knowledge on the management of disaster victims, Hospital Belén de Trujillo. The sample universe was made up of 28 nurses from the emergency service, the questionnaire "Socio-labor factors and the nurse's knowledge on handling disaster victims in the emergency service was applied to the Nursing Professional, Hospital Belén de Trujillo, where the following results were obtained: Socio-Labor Factors: age obtained 53.6% (31 to 40 years), time of service with 67.9% (more than 10 years) and 71.4% have specialty and 67.9% of the nurses obtained good knowledge. Concluding that there is a significant relationship between knowledge and socio-labor factors on the management of disaster victims of the emergency service of the Hospital Belén de Trujillo.